Roles of demographics, anthropometric and metabolic syndrome on cognition among mid adults from rural population in Nigeria - Valentine A Ucheagwu; Cyriacus Ajaelu; Paul C Okoli; Jesse Ossai; Philip C Ofojebe; Rita Ugokwe- Joseph (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2019)
There is increased interest in cognitive aging among experts in brain sciences and gerontology as a result of improvement in health sciences leading to longeveity. However, there are very limited studies on this area in Nigeria and some parts of Africa. Our study was to contribute to this area of science with African population, hence we investigated the roles of demographics, anthropometry and metabolic syndrome (Mets) on cognition in mid adults from rural part of Nigeria. Our participants were 172 middle aged adults from a rural community in Anambra state Nigeria.